Nitric oxide in exercise physiology: past and present perspectives - Mueller, Breanna J.; Roberts, Michael D.; Mobley, Christopher B.; Judd, Robert L.; Kavazis, Andreas N. (Frontiers in Physiology, 2025)
Nitric oxide (NO) is a ubiquitous signaling molecule known to modulate various physiological processes, with specific implications in skeletal muscle and broader applications in exercise performance. This review focuses on the modulation of skeletal muscle function, mitochondrial adaptation and function, redox state by NO, and the effect of nitrate supplementation on exercise performance. In skeletal muscle function, NO is believed to increase the maximal shortening velocity and peak power output of muscle fibers. However, its effect on submaximal contraction is still undetermined. In mitochondria, NO may stimulate biogenesis and affect respiratory efficiency. NO also plays a role in the redox state within the skeletal muscle, partially through its interaction with respiratory chain enzymes and transcriptional regulators of antioxidant production. Nitrate supplementation leads to an increased bioavailability of NO in skeletal muscle. Thus, nitrate supplementation has been investigated for its ability to impact performance outcomes in endurance and resistance exercise. The effect of nitrate supplementation on endurance exercise is currently indecisive, although evidence indicates that it may extend the time to exhaustion in endurance exercise. Alternatively, the effect of nitrate supplementation on resistance exercise performance has been less studied. Limited research indicates that nitrate supplementation may improve repetitions to failure. Further research is needed to investigate the influence of training status, age, sex, and duration of supplementation to further elucidate the impact of nitrate supplementation on exercise performance.